DEVELOPMENT OF INSTRUMENTS FOR SUSTAINABLE ENTREPRENEURIAL ACTIVITIES: IN THE PERCEPTIONS OF ENTREPRENEURSHIP STUDENTS - Kartika Nuringsih; Edalmen Edalmen (Graduate Program of Universitas Tarumanagara, 2024)
As appreciation for achieving the SDGs agenda, a study was carried out to produce sustainable entrepreneurship activity instruments. This process adopts a model previously prepared by Schlange in 2006 with using a triple bottom line framework. The sustainable entrepreneurship activity construct consists of three dimensions including economic, ecological and social activities with totally 18 indicators. This study involved 99 entrepreneurship students as respondents with the overall results of the indicators meeting the Cronbach's Alpha and composite reliability criteria, however the results of the convergent and discriminant validity tests were not completely valid. The results show that sustainable entrepreneurship has not been perceived ideally by respondents. There is a need to increase education, especially regarding ambiguous indicators. The implications of these results are applied to curriculum development as a value for universities in appreciating the goals of sustainable development.